Feminism : perspectives, stereotypes/misperceptions and social implications - Stroud, Pearce (Women's issues., 2014)
In this book the authors present current research in the study of feminism. Topics discussed in this compilation include the feminist focus on women and substance abuse treatment; the question of whether or not purely female societies can truly exist; women in elite positions within medicine; black women and their situation of discrimination and vulnerability in Brazil; the impact of migration on the reconfiguration of family dynamics; feminism and difference; theorizing African feminism; gender stereotypes and the effect on women's persistence in STEM fields; and an antidote for global femini.